The modern C++ challenge become an expert programmer by solving real world problems - Bancila, Marius (Packt Publishing, 2018)
Annotation
Includes bibliographical references. - Online resource; title from title page (Safari, viewed June 29, 2018)
Keywords: C++ (Computer program language); Computer programming; C++ (Langage de programmation); Programmation (Informatique); computer programming